A nonsense variant in the KRT14 gene in a domestic shorthair cat with epidermolysis bullosa simplex. (13th July 2020) - Dettwiler, M.; Leuthard, F.; Bauer, A.; Jagannathan, V.; Lourenço, A. M.; Pereira, H.; Leeb, T.; Welle, M. M.
Summary: Epidermolysis bullosa simplex (EBS) is a hereditary blistering disease affecting the skin and mucous membranes. It has been reported in humans, cattle, buffaloes and dogs, but so far not in cats. In humans, EBS is most frequently caused by variants in the KRT5 or KRT14 genes. Here, we report a case of feline epidermolysis bullosa simplex and describe the causative genetic variant. An 11‐month‐old male domestic shorthair cat presented with a history of sloughed paw pads and ulcerations in the oral cavity and inner aspect of the pinnae, starting a few weeks after birth. Clinical and histopathological findings suggested a congenital blistering disease with a split formation within the basal cell layer of the epidermis and oral mucous epithelium. The genetic investigation revealed a homozygous nonsense variant in the KRT14 gene (c.979C>T, p.Gln327*). Immunohistochemistry showed a complete absence of keratin 14 staining in all epithelia present in the biopsy. To the best of our knowledge, this is the first report of feline EBS, and the first report of a spontaneous pathogenic KRT14 variant in a non‐human species. The homozygous genotype in the affected cat suggests an autosomal recessive mode of inheritance.